Ownership structured firms in Malaysia: audit committee characteristics and audit fees / Norziaton Ismail Khan, Susela Selvaraj Devi and Meng Chan Wai - Ismail Khan, Norziaton; Selvaraj Devi, Susela; Wai, Meng Chan (Penerbit UiTM, 2019)
The political economy shaped the ownership structure of corporations in Malaysia. The rapid growth of the economy has not diluted the concentrated ownership structure in the Malaysian firms. Malaysia has its own unique feature of ownership structured firms which can be divided into politically connected (PCON) firms, institutional ownership and managerial ownership (INST&MGRL) firms, and family ownership (FAMILY) firms. The purpose of this paper is to investigate whether PCON, INST&MGR and FAMILY firms are associated with higher audit fees. This study also examines the association between audit committee characteristicsIND, DIL and EXP and audit fees based on the revamped Bursa Listing Requirementsin 2008, which focus on audit committee characteristics. Using data from 567 firm-year observations from years 2008 to 2010, we find that PCON firms pay higher audit fees than INST&MGRL and FAMILY firms. Further, the association between audit committee IND, DIL and EXP and audit fees is positive and significant for PCON firms, suggesting that the government intervention is expected to produce better governance and improve the firm’s business performance. Thisis because the government has given much attention and initiatives to ensure that these firms perform in an effective way and assist the government to improve the economic growth.